Efficacy of oseltamivir-peramivir combination therapy compared to oseltamivir monotherapy for Influenza A (H7N9) infection: a retrospective study. Issue 1 (December 2015) - Zhang, Yan; Gao, Hainv; Liang, Weifeng; Tang, Lingling; Yang, Yida; Wu, Xiaoxin; Yu, Liang; Chen, Ping; Zheng, Shufa; Ou, Huilin; Li, Lanjuan
Abstract Background Since the novel H7N9 avian influenza outbreak occurred in China in 2013, neuraminidase inhibitors (NAIs) such as oseltamivir and peramivir have been used as first-line drugs to treat the influenza virus infection. This study aimed to compare the efficacy of oseltamivir-peramivir combination therapy versus oseltamivir monotherapy. Methods A retrospective study of 82 H7N9 confirmed patients was conducted by reviewing medical charts at the First Affiliated Hospital of ZheJiang University in China from April 1, 2013 to Feb 28, 2014. The patients' clinical information was collected systematically, and we compared the virology and clinical data between oseltamivir monotherapy group (43 patients) and oseltamivir-peramivir combination group (39 patients). Results The median duration from NAIs administration to H7N9 virus-negative in oseltamivir monotherapy group and oseltamivir-peramivir combination group was 6.50 and 7.00 days (p >0.05), respectively. The median decline of Day 2 to Day 0 (initiation of NAIs therapy) viral load was 0.00 and 0.69 log10 copies/μl (p >0.05) respectively in the monotherapy vs. combination therapy groups. The incidence of new Acute Respiratory Distress Syndrome during NAI administration was 63.89 and 77.78 % (p >0.05); while the mortality rates were 25.58 and 43.59 % (p >0.05) in the oseltamivir group vs. oseltamivir-peramivir group. Conclusions Our results suggest that in adults with H7N9 virus infection, the use of oseltamivir-peramivir combination therapy was not superior to oseltamivir monotherapy.